Implementação de uma API para emular o kernel de tempo real RTXC no Linux/GNU visando aplicações multicore - Consiglieri, Daniel Sant´Anna (Universidade Federal de São Carlos, 2017)
The advent of multicore processors represented a major advance in the performance of parallel computing. Embedded systems following this trend have improved the computing power available for real-time systems, enabling the GNU/Linux development chain. Consolidated to more than twenty years in the Linux environment. In order to emulate the RTXC kernel, an API-RTXC-Linux was written in C and obtained deterministic results as well as homogeneous distribution for the response time of implemented calls, being possible its use for real-time applications.
Keywords: Emulador; Sistema de tempo-real; Sistemas embarcados; Kernel RTXC; Multicore; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO